Effect of storage temperature on somatic cell count of buffalo milk using direct microscopic method - BISWAS, SUMAN; MUKHERJEE, REENA; MAHTO, RAJNI PRABHA; DE, UJJWAL K (The Indian Journal of Animal Sciences, 2016)
This study was made to determine the effect of storage temperature and storage time on somatic cell counts (SCCs) in buffalo milk samples from quarters with no signs of clinical mastitis. The critical limit of SCC in raw buffalo milk is around 400,000 cells/mL. SCCs were measured in 32 Murrah buffalo milk samples by direct microscopic method. Milk samples were grouped from high score (> 3.50×105 cells/mL) to low score (< 1.50×105 cells/mL) according to the SCC. Each milk sample was divided into 3 aliquots and stored at 3 different temperatures (4°C, 21°C and 37°C). The SCC was recorded every hour up to 4 h and every 2 h up to 12 h. Storage of buffalo milk with a high SCC for 4 h at 4°C and 2 h at both 21°C and 37°C, respectively, decreased the log10 value of SCC compared to fresh milk. The log 10 value of buffalo milk SCC was lower after 1 h of storage than that determined for fresh milk at any tested temperature in low SCC samples. The results sugges that irrespective of storage temperature, buffalo milk samples should not be stored for more than 2 h before measurement of SCC by direct microscopic method.